The First Genetic Map in Sweet Osmanthus (Osmanthus fragrans Lour.) Using Specific Locus Amplified Fragment Sequencing - He, Yanxia; Yuan, Wangjun; Dong, Meifang; Han, Yuanji; Shang, Fude (Frontiers in Plant Science, 2017)
Osmanthus fragrans is an ornamental plant of substantial commercial value, and no genetic linkage maps of this species have previously been reported. Specific-locus amplified fragment sequencing (SLAF-seq) is a recently developed technology that allows massive single nucleotide polymorphisms (SNPs) to be identified and high-resolution genotyping. In our current research, we generated the first genetic map of O. fragrans using SLAF-seq, which is composed with 206.92 M paired-end reads and 173,537 SLAF markers. Among total 90,715 polymorphic SLAF markers, 15,317 polymorphic SLAFs could be used for genetic map construction. The integrated map contained 14,189 high quality SLAFs that were grouped in 23 genetic linkage groups, with a total length of 2962.46 cM and an average distance of 0.21 cM between two adjacent markers. In addition, 23,664 SNPs were identified from the mapped markers. As far as we know, this is the first of the genetic map of O. fragrans. Our results are further demonstrate that SLAF-seq is a very effective method for developing markers and constructing high-density linkage maps. The SNP markers and the genetic map reported in this study should be valuable resource in future research.